Effects on natural seed regenerated Silver birch (Betula pendula Roth) and Downey birch (Betula pubescens Ehrh) by mechanical soil scarification and environmental factors - Karlsson, Oskar (2022)
The awareness of forest biodiversity as well as the demand for a higher proportion of deciduous tree species in Swedish forests increases. As such, focus is shifting towards the management of naturally seed regenerated Silver birch (Betula pendula Roth) and Downey birch (Betula pubescens Ehrh). It is therefore essential to extend the knowledge of how birch seed regeneration is affected by management interventions as well as biotic and abiotic environmental factors. I selected 20 sites in northern Sweden that had been clear-cut between 2014 – 2019. Half of the sites had undergone mechanical scarification within two years after clear-cut. On all sites, a selection of biological, edaphic, and geographical factors along with naturally seed regenerated birch seedlings and saplings present were inventoried using a quadratic systematic grid of plots. Results showed that there was a trend towards a higher number of birch seedlings and saplings on not scarified sites. Also on not scarified sites, there were significantly shorter distances to seed trees and higher moss coverage in comparison to scarified sites, which according to correlation analysis increased number of seed regenerated birch seedlings and saplings. This work illuminates the importance of regarding multiple factors when regenerating birch by seed. Further research that captures the effect by a wide selection of biotic and abiotic environmental factors together with management interventions on birch seed regeneration is needed.